Rancang Bangun Aplikasi Pelayanan Dan Rekam Medis Calon Tenaga Kerja Indonesia Pada AL-HUDA MEDICAL CENTER - Ramdhani, Hilmy Nur; Sunarto, Dewiyani; Romeo, Romeo (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Al-Huda Medical Center is special unit of Al-Huda hospital which manages check-up service for Prospective Indonesian Migrant Worker (CTKI). Al-Huda Medical Center wants to improve the service process and medical record of CTKI using computer system. There are five main problems found in the field regarding this matter, they include (1) all data reports consisting of registration to medical record database is still in paper-based documents, (2) the registration number is processed manually, (3) there is no barcode in health certificate, (4) specimen is labelled using handwriting (5) registration report, medical record, form, and film paper is done manually in terms of calculation and writing. The solution offered for the aforementioned problems is developing a web-based application which is able to manage service process, medical record, and report. Furthermore, this application provides health certificate which fulfills the standardization of the destination country of CTKI. This application also offers the more accurate reports compared to paper-based documentation.